Psychology for language teachers : - Williams, Marion (Cambridge university press, 2002)
This book examines the field of educational psychology and considers how insights from the discipline may be of some use in language teaching. Areas considered in the book include approaches to learning, motivation, attribution, mediation, the role of the individual, the cognitive demands of tasks and the learning environment.